Hidradenitis suppurativa and psoriasis: the odd couple - Macca, Laura; Li Pomi, Federica; Ingrasciotta, Ylenia; Morrone, Pietro; Trifirò, Gianluca; Guarneri, Claudio (Frontiers in Medicine, 2023)
Psoriasis and hidradenitis suppurativa are chronic inflammatory skin diseases that can develop together, negatively impacting on the patient’s quality of life. We aimed to review the most up-to-date information regarding the epidemiology, pathogenesis, clinical presentation and possible therapeutical choices in patients with both psoriasis and hidradenitis suppurativa, thus linking these two autoimmune and autoinflammatory conditions. A narrative review of articles dating from 2017 to 2022 has been performed using the PubMed database. We analyzed the case reports and case series found in the literature regarding patients who suffered from both psoriasis and HS. Psoriasis arose before hidradenitis suppurativa in the majority of cases, while only a minority of them had hidradenitis suppurativa before psoriasis. Interestingly, some patients suffered from paradoxical hidradenitis suppurativa following biological therapy administered to treat the already present psoriasis. Lastly, new biological drugs have been marketed with great success for the outcome of psoriasis, but similar progress did not happen for hidradenitis. Novel therapeutic approaches and lines of research are needed for the treatment of these pathologies, even if concomitant, in order to improve patient’s quality of life.